2022
DOI: 10.55705/cmbr.2022.335753.1033
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of Bio-makers of Chloroquine resistance in Plasmodium falciparum Isolate from Gombe Local Government Area, Gombe State, Nigeria

Abstract: Chloroquine was one of the most cheapest and effective chemotherapeutic drugs for Plasmodium falciparum-malaria, but for a long, the drug has been officially withdrawn in almost all malariaendemic countries including Nigeria, due to the development of resistance by the parasite. Withdrawal of the drug may make the drug regains its efficacy. Therefore, this study aimed to determine the presence of Biomarkers associated with chloroquine resistance from Gombe Local Government Area, Gombe State, Nigeria after its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…However, the association of other polymorphisms in cis could have an impact on the severity of the disease. This research will serve as a platform for epidemiological and clinical studies to improve patient care in the Arab world and worldwide (33,34)…”
Section: Resultsmentioning
confidence: 99%
“…However, the association of other polymorphisms in cis could have an impact on the severity of the disease. This research will serve as a platform for epidemiological and clinical studies to improve patient care in the Arab world and worldwide (33,34)…”
Section: Resultsmentioning
confidence: 99%
“…As a commonly used device in clinical intensive care, the respiratory circuit is a multi-use apparatus, whose cleaning and disinfection effectiveness is directly associated with its sterilization quality and in turn, affects the anti-infection treatment. At present, monitoring the cleaning and disinfection effect is a key part of the medical device quality control process (22)(23)(24)(25). Microbial culture is now a highly accurate, common and simple clinical method for evaluating the effectiveness of cleaning and disinfection.…”
Section: Eric-pcr Results Of K Pneumoniaementioning
confidence: 99%
“…Moreover, although we did not measure IL-6 levels in this study, vitamin D supplementation is reported to decrease this inflammatory factor (33), and it is directly related to depression, which itself It is one of the main reasons for death in hemodialysis patients (34). According to Okereke and Singh, (2016), vitamin D deficiency can be a depression risk factor in late life (35)(36); thus, it is vital to note that cases with ESRD and hemodialysis are mostly middle-aged and older, and supplement therapy for these patients can have a central role in improving quality of their life.…”
Section: Vitamin D Significantly Improved Oxidative Stress and Inflam...mentioning
confidence: 87%